Social Identity and Consumer Boycott Participation in Indonesia: An Extension of Theory of Planned Behavior - Evelyn, Evelyn; Sekarasih, Laras (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Consumers around the world are increasingly turning to boycotts as a means of expressing their concerns or protests toward corporate practices perceived as unethical. In Indonesia, this form of activism has gained momentum, particularly among Muslims, where consumer boycotts have been in place in response to the Israel-Palestine conflict, especially since the conflict escalation in the last quarter of 2023. Using the extended version of the theory of planned behavior (TPB) by integrating social identity, this study examined how Muslim identification corresponds with consumers’ attitudes and perceptions to predict intention to boycott and actual boycott participation among Indonesian Muslims. The study employed an online survey distributed to a sample of 372 Muslim consumers from an online market research panel in Indonesia. Muslim identification was found to significantly predict attitude, subjective norms, and perceived behavioral control, both directly and indirectly. Of the three components of TPB, attitude emerged as the most influential predictor and mediating factor linking Muslim identity to both intention and behavior. The findings suggest the significant role of social identity which underlies consumer attitudes, subjective norms, and perceived behavioral control in predicting their intention and engagement in boycott behavior. Furthermore, this study offers practical implications for non-profit organizations, grassroot activists, and consumer educators who intend to run initiatives based on consumer activism. Abstracts are written in Indonesian and English with a space of 1.0 lines and a maximum of 200 words summarizing the contents of the paper, including hypotheses, research subjects, methodologies, and results.